(untitled) (Cardiovascular Journal, 2012)
Coronary artery disease (CAD) is one of the most important causes of morbidity and mortality worldwide despite considerable therapeutic advances that control the risk factors. Numerous clinical trials have shown an inverse association between high density lipoprotein cholesterol levels and the risk of coronary artery disease. So, high density lipoprotein has become a new therapeutic target after low density lipoprotein in the management of risk factors of coronary artery disease. In this review, we explore existing and future treatment strategies along with their benefits and failures which will guide our management strategy. HDL raising therapies showed very promising results in many clinical trials but larger clinical trials are ongoing DOI: http://dx.doi.org/10.3329/cardio.v5i1.12277 Cardiovasc. j. 2012; 5(1): 73-80